Fruit and Vegetable Wastes: Review of Nutritional Composition, Antimicrobial Potential, and Sustainable Applications in Malaysia - Poddar, Ruma; Kanathasan, Jayasree S; Ahmed, Idris Adewale (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Food waste, particularly from fruits and vegetables, represents a major environmental, economic, and social challenge worldwide. Fruit and vegetable peels, seeds, and trimmings are typically discarded, despite being rich in essential nutrients, dietary fibers, bioactive compounds, and minerals. Recent research highlights their potential as renewable resources for nutraceuticals, bioenergy, edible films, and antimicrobial agents. In Malaysia, the rapid expansion of the agro-industrial sector has increased fruit waste generation, especially from highly consumed products such as mango, watermelon, and rambutan. This paper reviews the proximate composition of common fruit and vegetable wastes and their potential applications in addressing food security, antimicrobial resistance, and sustainable waste management. The role of computational bioinformatics, molecular docking, and nanotechnology in enhancing the utilization of bioactive compounds from food waste is also discussed. The study underscores the importance of integrating proximate analysis with innovative biotechnological strategies to reduce municipal solid waste while contributing to public health and sustainable development goals.